Exploring the utility of the Nursing Role Effectiveness Model in evaluating nursing contributions in primary health care: A scoping review - Julia A. Lukewich; Joan E. Tranmer; Megan C. Kirkland; Anna J. Walsh (Wiley, 2019)
Abstract Aims To inform a discussion for the applicability of using the Nursing Role Effectiveness Model (NREM) in the primary health care setting through a synthesis of the literature that has used the model in all health care sectors. Design Scoping Review. Methods Articles were considered for inclusion if they discussed any aspect of the NREM in health care research that presented information related to any nursing regulatory designation, such as nurse practitioner (NP), registered nurse (RN), licensed/registered practical nurse (LPN/RPN) and considered both quantitative and qualitative study designs, including expert opinions and reports. Results A total of 22 articles that cited and/or used the NREM were identified in this review. Only two studies were focused in the primary health care setting. There is precedence for the use of the NREM to guide research in primary health care. The NREM should be modified to incorporate the unique characteristics of the primary health care setting.